6*(б -3)=10-2*(б+2)                  83+5*(у-3)=3*(8у-9)
6б-18=10-2б-4                         83+5у-15=24у-27
6б+2б=10-4+18                       5у-24у=-27-83+15
8б=24                                     -19у=-95
б=24:8                                    у=-95:(-19)
б=3                                        у=5                     
6*(3-3)=10-2*(3+2)                   83+5*(5-3)=3*(8*5-9)
0=0                                        93=93

Leave a Reply

Your email address will not be published. Required fields are marked *

coolessay discount code
sitemap28
sitemap1
sitemap21
sitemap46
sitemap49
sitemap4
sitemap8
sitemap27
sitemap62
Adblock detector